Toward fast charge extraction in all-inorganic CsPbBr3 perovskite solar cells by setting intermediate energy levels. (1st September 2018) - Liao, Guoqing; Duan, Jialong; Zhao, Yuanyuan; Tang, Qunwei
Graphical abstract: The TiO2 /CsPbBr3 and CsPbBr3 /carbon interfaces of all-inorganic PSC are modified by CQDs and RPQDs to extract electrons and holes, respectively. Highlights: All-inorganic CsPbBr3 solar cells are made by a multi-step solution-processable method. Intermediate energy levels are set at TiO2 /CsPbBr3 and CsPbBr3 /carbon interfaces. CQDs and RPQDs are used to extract electrons and holes, respectively. The optimized inorganic PSC yields an efficiency of 8.20% and improved stability. Abstract: Perovskite-structured cesium lead bromide (CsPbBr3 ) halide is a rising light harvester for perovskite solar cell applications due to its high absorption coefficient and stability upon heat and humidity attacks. However, the serious electron-hole recombination arising from large interfacial energy differences has markedly limited charge extraction for enhanced photovoltaic performances. Herein, we systematically study fast charge extraction at TiO2 /CsPbBr3 and CsPbBr3 /carbon interfaces by setting intermediate energy levels with carbon quantum dots and red phosphorus quantum dots, respectively. The interfacial radiative or trap-dominant recombination can be significantly suppressed owing to the boosted charge transfer ability as well as the passivation effect by incorporating the carbon quantum dots and red phosphorus quantum dots into solar cells. Finally, the optimal perovskite solar cell device achieves a maximized power conversion efficiency of 8.20% under one sun illumination in comparison with 6.37% for quantum dots-free solar cell. Moreover, the efficiency is reduced by only 3% upon persistent attack with 80% relative humidity over 1000 h, suggesting a good environmental tolerance to boost the commercialization.